Peran Kepemimpinan Visioner dan Transformasional Kepala Sekolah dalam Meningkatkan Mutu Tenaga Pendidik dan Tenaga Kependidikan - Tubagus Octafiani; Anis Zohriah; Universitas Islam Negeri Sultan Maulana (Journal on Education, 2023)
Objective Study is to find out the role of visionary and transformational leadership of school principals in implementing the vision and mission in improving the quality of teaching and educational staff at SDIT Al-Izzah and SDIT Widya Cendekia. As well as to find out the obstacles in the visionary and transformational leadership of the principal in implementing the vision and mission in improving the quality of teaching and educational staff at SDIT Al-Izzah and SDIT Widya Cendekia. This research method uses qualitative methods. The research was conducted at SDIT Al-Izzah and SDIT Widya Cendekia. The method of collecting data using interview techniques, observation and documentation.Results research shows that leadership visions and transformational principals at SDIT Al-Izzah in implementation vision and mission use increase stopenergy educator and education done by means of (1) improvement competence pedagogical, (2) competence personality teacher, (3) social competence of teachers, (4)increase professionality teacher, (5) monitoring and evaluation of activities. While SDIT Widyascholar implements it starting from analyzing deficiency, teacher needs from external and internal factors as well as improving teacher assignments, until a plan program for overcoming deficiency and problem faced by teachers. As for constraint implementation of energy quality improvement educator by head SDIT Al-Izzah Serang City (1) still lack experience the teachers, (2) lack experience technique communicate, (3) the amount teacher women image productive. Meanwhile, the obstacle faced by the head of SDIT Widya Cendekia is facilities limited, commitment teacherless well and still lack experience for teacher, Good Experience in the review area material.